2008
DOI: 10.1037/0022-0167.55.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Helping skills training for undergraduates: Outcomes and prediction of outcomes.

Abstract: The authors examined outcomes and predictors of outcomes for 85 undergraduates in 3 helping skills classes. After training, trainees used more exploration skills in helping sessions with classmates (as assessed by perceptions of helpees and helpers/trainees as well as behavioral counts of skills), were perceived by helpees as more empathic, talked less in sessions, conducted better sessions (from helpee and helper/trainee perspectives), and reported higher self-efficacy for using helping skills. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 36 publications
(59 reference statements)
10
87
1
1
Order By: Relevance
“…The outcome of training in each cohort as a whole was successful, but the patterns of change in skills (as rated by both trainees and their clients) differ between the cohorts. This is of particular interest given inconsistencies in the existing literature in addition to an increased demand for training in helping skills at the undergraduate level (Hill & Lent, 2006;Hill et al, 2008). Most importantly, undergraduate students significantly improved their skills in only nine weeks of training (time 3); moreover, during that time they were able to reach the level of graduate students' performance in some areas.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The outcome of training in each cohort as a whole was successful, but the patterns of change in skills (as rated by both trainees and their clients) differ between the cohorts. This is of particular interest given inconsistencies in the existing literature in addition to an increased demand for training in helping skills at the undergraduate level (Hill & Lent, 2006;Hill et al, 2008). Most importantly, undergraduate students significantly improved their skills in only nine weeks of training (time 3); moreover, during that time they were able to reach the level of graduate students' performance in some areas.…”
Section: Discussionmentioning
confidence: 90%
“…There is little study of undergraduates in training, which is increasingly becoming a critical and formative first contact with clinical training and one that is growing in demand (Hill et al, 2008). A current review by Hill et al (2008) found only five other studies related to the training of undergraduate students.…”
Section: Findings On Psychotherapy Trainingmentioning
confidence: 95%
See 3 more Smart Citations